Changes in the Lipid Profiles of Pre- and Post-Cholecystectomy Patients: A Systematic Review and Meta-Analysis: Lipid Profiles Pre- and Post-Cholecystectomy - Oktaviani, Jacinda Risha; Widjaja, Vivi; Pardede, Helena Tania Caroline (Universitas Airlangga, 2025)
Background: Patients with gallstones often exhibit irregular lipid profiles, such as hyperlipidemia, which may cause various morbidities. Gallstone treatment by cholecystectomy can alter bile acids, subsequently impacting the lipid profile. This study aimed to analyze the effects of cholecystectomy on lipid profiles. Methods: This systematic review and meta-analysis adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PubMed, Cochrane, ProQuest, and Google Scholar were utilized to discover prospective or retrospective cohort studies, cross-sectional studies, and non-randomized trials. The inclusion criteria were studies comparing lipid profiles pre- and post-cholecystectomy in the same patients, conducted on humans, and published in English with full text available. Abstracts from conferences, case studies/series, review articles, letters, editorials, and research published in languages other than English were excluded. A meta-analysis was conducted on patient outcomes using random- or fixed-effect models to generate pooled odds ratios (OR) with 95% confidence intervals (CI). A significant change in lipid profiles was indicated by p<0.05. Results: There were 17 selected studies involving 1,691 participants. Within less than a week, cholecystectomy significantly decreased total cholesterol and low-density lipoprotein (LDL). During one-month follow-ups, cholecystectomy significantly increased high-density lipoprotein (HDL) while reducing other lipid profile markers, including total cholesterol, LDL, and triglycerides. During follow-ups beyond one month, there were no significant changes in lipid profiles. Conclusion: Cholecystectomy decreases total cholesterol and LDL within days and improves all lipid profile markers a month post-surgery. Beyond one month, it does not exhibit significant changes in lipid profiles. Highlights: 1. This is the first systematic review and meta-analysis that provides valuable insights into the effects of cholecystectomy on lipid profile. 2. This study offers a foundation for more effective postoperative management strategies to mitigate cardiovascular disease risks. 3. This study may also be the foundation of theories regarding the advantage of cholecystectomy for improving lipid profile.